Controlled-release urea application and optimized nitrogen applied strategy reduced nitrogen leaching and maintained grain yield of paddy fields in Northwest China - Liu, Ruliang; Wang, Ying; Hong, Yu; Wang, Fang; Mao, Xinping; Yi, Jun (Frontiers in Plant Science, 2023)
Nitrogen loss from paddy fields contributes to most of the nitrogen pollution load in the Ningxia Yellow River irrigation area, threatening the water quality of the Yellow River. Consequently, optimizing the nitrogen management practices in this area is essential, which can maintain paddy grain productivity and reduce nitrogen loss simultaneously. Five treatments with different nitrogen application rates and nitrogen fertilizer types were set in this study, including conventional urea application with zero nitrogen application rate (CK, 0 kg hm-2), nitrogen expert-based fertilization application strategy (NE, 210 kg hm-2), optimized nitrogen fertilizer application strategy recommended by local government (OPT, 240 kg hm-2), and farmer's experience-based nitrogen fertilizer application strategy (FP, 300 kg hm-2), and controlled-release urea application (CRU, 180 kg hm-2). The data from one growth season field experiment in 2021 revealed the dynamics of nitrogen concentration, paddy yield and its nitrogen uptake characteristic, and nitrogen balance in the paddy field under different nitrogen application practices. Most nitrogen leaching was observed during the seedling and tillering stages in the form of nitrate nitrogen (NO3--N). Compared with the FP, the CRU and OPT significantly reduced the nitrogen concentrations of total nitrogen (TN), ammonium nitrogen (NH4+-N), and NO3--N in the surface and soil water and reduced the nitrogen leaching at 100 cm soil depth. Meanwhile, the paddy grain yield in CRU (7737 kg hm-2) and OPT (7379 kg hm-2) was not significantly decreased compared with FP (7918 kg hm-2), even though the nitrogen uptake by grain and straw was higher in FP (135 kg hm-2) than in other treatments (52.10~126.40 kg hm-2). However, the grain yield in NE (6972 kg hm-2) was decreased compared with the FP. The differences in grain yield among these treatments were mainly attributed to the ear number and grain number changes. Also, the highest nitrogen use efficiency (40.14%), apparent nitrogen efficiency (19.53 kg kg-1), and nitrogen partial productivity (43.98 kg kg-1) were identified in CRU than in other treatments. Considering increased grain yield and reducing nitrogen loss in the paddy field simultaneously, the treatments of CRU and OPT were recommended for nitrogen fertilizer application in the study area.